Analisis Gaya Kepemimpinan Kepala Bidang Kemetrologian Dinas Koperasi, Usaha Kecil Menengah, Perindustrian dan Perdagangan Kabupaten Nunukan - Kumaidi Harianto; Nur Wulan Intan Palupi (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to identify how the use of leadership styles in the Field of Metrology. The Office of Cooperatives, Small and Medium Enterprises, Industry and Trade of Nunukan Regency is one of the local government agencies engaged in the field of Cooperatives, Small and Medium Enterprises, Industry and Trade, including formulating policies based on their scope, implementing policies according to the scope below, and carrying out monitoring, evaluation and reporting according to their scope, carrying out service administration according to their scope and carrying out other functions given by the local government related to their duties and authorities. The Metrology Division is responsible for implementing policies that focus on the implementation of metrology in terms of calibration and recalibration services, metrology supervision and investigation activities, facilities and infrastructure and presentation of data and information in the field of metrology. This study uses a qualitative method using a descriptive approach. This approach aims to explain and describe the problems faced while offering solutions to the issues raised. Data were collected through questions and answers and observations to understand the use of leadership styles in government institutions in the region. This study took five respondents who worked in the Metrology Division. The results of the study showed that 4 (four) types of leadership models were obtained which were used in the Metrology Section, namely directive, supportive, participative, and achievement-oriented leadership, with the participative leadership model as the most dominant.